Israel`s evolving approach to citizens who have returned to the diaspora - Gold, Steven J. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article examines the means by which Israel has sought to fulfill the contradictory goals involved with maintaining contacts with emigrants while simultaneously sustaining a national mission that asserts Jews can only achieve fulfilment, security, and self-determination by residing in their own country. It describes three successive approaches by which Israel and the larger global Jewish community have addressed the challenges associated with Israeli emigration. These are condemnation, pragmatic acceptance, and the assent of the Israeli American Council.
Keywords: Ingathering of the exiles; diaspora Jews; Israeli emigration; Emigrant organizations; Israeli Americans